Sensory marketing importance in ham stores: Viandas Hacienda Zorita case in Salamanca - Pilo Castellano, Lucía; Hernández Zelaya, Sandra Lizzeth (IROCAMM - International Review Of Communication And Marketing Mix, 2021)
Introduction: Sensory marketing is an increasingly popular tactic in a marketing strategy, commonly used in commercial establishments, with the aim of capturing the attention of consumers and making them loyal. Many shops try to attract consumers to the interior of the establishments and thus invite them to buy using different sensory activities. Objective: Through this study, it is intended to analyze the sensory marketing strategies of ham stores and especially those used by Viandas Hacienda Zorita, to try to understand the reasons that lead this company to stand out as a store specialized in ham sales in Spain. Methodology: The study includes the implementation and analysis of both qualitative and quantitative research techniques, observation technique such as interviews with experts and the application of a survey to 150 Spanish consumers. Results: The study highlights the usage of sensory marketing and its effectiveness to generate a more attractive atmosphere and stimulate the senses in this particular sector. The main conclusions emphasized are the importance of sensory marketing as a commercial tool in Ham stores, in particular appealing to the sense of sight and smell in these stores is identified as very relevant.